Regional science in Germany during the nineties — Are German publication patterns different? - Royuela, Vicente; Suriñach, Jordi; Duque, Juan Carlos (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
This article compares the German research in regional science in the period 1991–2000 with research that has been carried out internationally and in particular with that developed in continental Europe. We have done this on the basis of the publications in a sample of nine top regional and urban international journals. We found that the publication patterns of German contributions were very similar to international patterns, though there were several interesting peculiarities. Results show that Germany's share in regional and urban research is relatively high, fourth in the world.